External beta dose rates to mineral grains in shell-rich sediment - Cunningham, Alastair C. (Ancient TL, 2016)
Luminescence dating methods make use of the infinite-matrix assumption to simplify dose rate calculations. This works well when the sediment grain size is much smaller than the range of beta electrons in sediment (∼3 mm). However, shell material introduces complexity in the beta dose rate calculations, because it creates low-dose-rate zones where no mineral grains are present. This phenomenon introduces an error in the estimated beta dose rate, whether or not the shells are included in the beta dose-rate measurements. The magnitude of the error depends on the size and shape of the shell material, and the quantity of it. Here, this relationship is modelled using Monte Carlo radiation transport software. The model indicates that for shell masses below 25%, accurate estimates of beta dose rate are readily obtained from: 1) the infinite matrix dose rate of the bulk material (including shells) when shell fragments are small (< ∼0.001 cm3 ); and 2) the infinite matrix dose rate of the sandy fraction (without shells) when shell fragments are larger (> ∼1 cm3 ). Between these extremes of shell size, e.g. for shell-hash samples, a significant correction to the measured beta dose rate is necessary